Promotion of public-bred hybrids of field crops - Rao, S. K.; Kalloo, G.; Khare, Dhirendra; Jawaharlal Nehru Agricultural University (New Delhi : Studium Press (India), 2010)
With reference to India; papers presented at a seminar organized by Jawaharlal Nehru Agricultural University on February 23-24, 2008.
Includes bibliographical references and index.
Keywords: Field crops -- Hybridization -- India